The use of point counterpoint strategy in teaching EFL students’ writing skill at Madrasah Aliyah Negeri (MAN) 5 Bireun - Abdullah Abdullah; Usman Kasim; Saiful Marhaban (Universitas Syiah Kuala, 2021)
This study aimed to find out the use of point-counterpoint strategy to improve students’ writing skills on discussion text for the second-grade students of Madrasah Aliyah Negeri (MAN) 5 Bireuen. This research used a quantitative method. The research subjects were 42 students from XI MIPA 1 and MIPA 2. Class XI MIPA 1 was an experimental group and Class XI MIPA 2 was a control group. Both classes were selected for students’ equal ability. The instruments used to collect the data were tests; pretest and posttest and questionnaire. The writing test was used for pretest and post-test. The data collected were analyzed using descriptive statistic to find the mean scores of the two classes. The mean score of the pretest in the experimental class was 63.61 and the mean score of the posttest in the experimental class was 77. Meanwhile, the mean score of the pretest in the control class was 63.80 and the mean score of the posttest in the control class was 74.47. The mean score of the experimental class was higher than the control class. Accordingly, the hypothesis of this research was accepted. In the questionnaire, the researchers found that almost all students choose “agree” toward the Point-Counterpoint strategy in writing discussion text.